Pyrococcus furiosus flagella: biochemical and transcriptional analyses identify the newly detected flaB0 gene to encode the major flagellin - Näther-Schindler, Daniela J.; Schopf, Simone; Bellack, Annett; Rachel, Reinhard; Wirth, Reinhard (Frontiers in Microbiology, 2014)
We have described previously that the flagella of the Euryarchaeon Pyrococcus furiosus are multifunctional cell appendages used for swimming, adhesion to surfaces and formation of cell-cell connections. Here, we characterize these organelles with respect to their biochemistry and transcription. Flagella were purified by shearing from cells followed by CsCl-gradient centrifugation and were found to consist mainly of a ca. 30 kDa glycoprotein. Polymerization studies of denatured flagella resulted in an ATP-independent formation of flagella-like filaments. N-terminal sequencing of the main flagellin revealed an unexpected N-terminus. Therefore, we resequenced the respective region of the genome, thereby discovering that the published genome sequence is not correct. A total of 771 bp are missing in the data base, resulting in the fact that a total of three flagellin genes are present. To keep in line with the earlier nomenclature we call these flaB0, flaB1, and flaB2. Very interestingly, the previously not identified flaB0 codes for the major flagellin. Transcriptional analyses of the newly defined flagellar operon identified various different transcripts depending on the growth phase.